POLA HUBUNGAN PATRON-CLIENT PADA MASYARAKAT NELAYAN “PUKAT CINCIN MINI“ DI BANDAR LAMPUNG - Tajerin, Tajerin (Jurnal Masyarakat dan Budaya, 2004)
Patron-Client relation in a fishing communities is a kind of work relationship among capital owners, fishing gear and fishermen that is herrited and institutionalized. It was demonstrated by resistances to institutional innovation in small scale fishermen societies. The research was a case study of Bandar Lampung fishermen who used mini purse seine. Purposive sampling technique was used with pengambek, juragan and pandega as respondents. Qualitative method was used as data analysies. The result of the study showed that two patterns of patron-clinet relationship indicated in this research, those were pengambek and juragan relation focused on capital and market structures. Those patterns of relation, pengambek, juragan and pandega tend to maintain patron-client relation.